Surveillance of Bloodstream Infections in Belgian Hospitals - Annual report 2023 , Data up to and including 2022 - Mariken Vercruyce; Louise Vaes; Nathalie Shodu; Karl Mertens (Sciensano, 2024)
These 2022 results of the National Surveillance of Bloodstream Infections (NSIH-SEP) show a hospital-associated bloodstream infection (HABSI) cumulative incidence of 5.4 patients with HABSI per 1,000 hospitalisations, and a HABSI incidence density of 9.2 episodes per 10,000 patient-days (pd). Incidence of Central line-associated bloodstream infection (CLABSI) in 2022 was 2.4 episodes per 10,000 pd. Generally, hospital-wide incidences of HABSI show decreasing trends since 2020, however their 2022 results remain higher as compared to pre-COVID19 levels (2019 and before). ICU-associated BSI cumulative incidence in 2022 was 18.6 patients with ICU-BSI per 1,000 ICU hospitalisations, and ICU-BSI incidence density in 2022 was 40 episodes per 10,000 ICU pd. ICU-associated CLABSI incidence density in 2022 was 15.5 episodes per 10,000 ICU pd. Generally, incidences of ICU-BSI are multiple times higher as compared to hospital-wide HABSI. As with hospital-wide HABSI, ICU-BSI incidences also show decreasing trends since 2020, but their 2022 incidence also remains higher as compared to 2019 and before. Forty–three percent of hospital-wide HABSI cases and even 66% of ICU-BSI cases were linked to an invasive device whether directly (central and other catheters) or indirectly (urinary catheter, endotracheal tube). Of these, exposure to central vascular catheter remains the most frequently reported origin of HABSI cases both hospital-wide (26% of HABSI) as well as ICU-only (39% of ICU-BSI). This report also presents for the first time results on the incidence of HABSI cases associated to the use of peripheral line, their 2022 incidence density being 0.23 episodes per 10,000 pd (hospital-wide) and 0,38 episodes per 10,000 ICU pd (ICU-specific). Incidence of these peripheral line-associated HABSI is much lower as compared to CLABSI incidence, however this type of HABSI is possibly underreported in the current version of the NSIH-SEP surveillance protocol. In 2022, the most commonly micro-organisms (MO) isolated from hospital-wide HABSI cases were E. coli, S. aureus, and S. epidermidis, this last MO also being the most commonly isolated from hospital-wide CLABSI cases. Long-term increasing trends can be observed for hospital-wide HABSI incidences due to E. coli, K. pneumoniae, and E. faecium. The trend of hospital-wide CLABSI due to S epidermidis is also increasing since 2016, while it is decreasing for CLABSI due to S aureus. We also observe a long-term decreasing trend in the prevalence of methicillin-resistant S aureus (MRSA). While the NSIH-SEP register was the first national Healthcare-associated infection surveillance to migrate to the Healthdata environment in 2017, its actual tools for data collection and centralized data processing and results reporting are now in need of revision. Tools for data collection need to be harmonized with other registers on BSI/AMR such as surveillance of antimicrobial resistance and of ICU-acquired infections, and also need to be adapted towards automated collection of hospital data where possible. Healthdata tools for centralized data processing and reporting of national NSIH-SEP results should also be automated where possible. Next to this, recent and ongoing technical problems of data collection and analysis environments of the Healthdata platform have resulted in unnecessary delays in the reporting of these results; Sciensano and its Healthdata service are therefore recommended to prioritize on the resolution of these issues, and also to elaborate alternative procedures for data collection and reporting such that deadlines for annual publication of national surveillance results remain unaffected. Another reason for delayed publication of these national results is the late submission of surveillance data for a substantial number of hospitals. A discussion on the (suspension of) the mandatory status of the NSIH-SEP surveillance might be needed, as the delays now observed in collecting and validating surveillance results from many hospitals might as such be avoided. These results show that central catheter is the most frequently documented HABSI origin in 2022, and that CLABSI incidence in 2022 remains at an increased level as compared to pre-COVID19 years. We therefore recommend a strong focus on the prevention of this type of HABSI, in the first place by freeing resources for the development of national recommendations on catheter use, and for the follow-up of their compliance on a national level. The NSIH-SEP surveillance should also be adapted such that it allows a more detailed look into catheter infections, for example by adding indicators on catheter use in hospitals in Belgium, and also by additionally documenting exposure to peripheral line exposure for each HABSI episode.
Keywords: Bloodstream infections; healthcare associated infections